Influence of Temperature and Time Carbonization on Calorific Value of Charcoal Briquette Raw Materials Areca Nut Husk - Riski Camarta; Hendri Nurdin; Nelvi Erizon; Andril Arafat (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2020)
Areca nut husk is one type of biomass that can be used as raw material for briquettes as an alternative energy producer. Charcoal briquettes are solid fuels that can be used as alternative fuels in an effort to meet energy needs. This study aims to assess the quality of areca nut charcoal briquettes through carbonization at temperatures of 200 ° C, 250 ° C, 300 ° C, 350 ° C and 400 ° C at holding times for 30, 60 and 90 minutes. The study was conducted by pyrolysis of areca nut briquettes which had been formed and dried. Testing the quality of charcoal briquettes includes calorific value analysis. The results of this study indicate the highest heating value of coir briquette charcoal is at carbonization temperature of 300 ° C for 60 minutes at 20979,13632 KJ/Kg. Serat buah pinang merupakan salah satu jenis biomassa yang dapat dimanfaatkan menjadi bahan baku briket sebagai penghasil energi alternatif dalam mengurangi penggunaan bahan bakar fosil (minyak bumi). Briket arang merupakan bahan bakar padat yang dapat dijadikan sebagai bahan bakar alternatif dalam upaya untuk dapat memenuhi kebutuhan energi. Pembuatan briket menggunakan perekat tapioka dengan komposisi biomassa dan perekat sebanyak 80% dan 20%. Penelitian ini bertujuan untuk mengkaji kualitas briket arang serat buah pinang melalui proses karbonisasi pada temperatur 200°C, 250°C, 300°C, 350°C dan 400°C pada waktu tahan selama 30, 60 dan 90 menit. Pengujian kualitas briket arang meliputi analisis nilai kalor. Hasil penelitian ini menunjukkan nilai kalor briket arang serat buah pinang tertinggi terdapat pada temperatur karbonisasi 300°C selama 60 menit sebesar 20979,13632 KJ/Kg.